EVALUATION OF BIOLOGICAL ACTIVITY OF TAR EXTRACTED FROM PINUS BRUTIA AND CEDRUS LIBANI FROM TURKEY - Dalkilic, Semih; Dalkilic, Lutfiye Kadioglu; Celik, Aysenur; Atessahin, Dilek Arslan; Mulayim, Sefa; Kucuktufekci, Mert Can; Gulacar, Ozgecan (Pakistan Botanical Soc, 2024)
Tar is an example of an herbal product in folk medicine obtained from Pinus brutia and Cedrus libani. To obtain tar, old trees with thick trunks that are suitable for kindling are preferred. Tar is used not only in traditional medicine but also in antitumor and antimicrobial studies. This study aims to investigate the apoptotic, cytotoxic and antimicrobial - activity of tars obtained from different tree species in Turkey/Karaman, located in the Central Anatolian Region of Turkey. This study used pine tar consisting of C. libani, natural tar formed by its solidification, and wood tar extracts obtained from the P. brutia tree. Their cytotoxic activity on MDA-MB-231, MCF 7, and HepG2 cell lines was determined for the first time by the MTT method and double staining on cell lines, and their antimicrobial and antioxidant activities were also investigated. The data of the study revealed that these extracts exhibited remarkable cytotoxic effects on cell lines with varying degrees. Also, whether cells undergo apoptosis or necrosis was examined by double staining. In this respect, it is predicted that tar extracts are strategically important and may be used for the treatment of cancer.
Keywords: Cytotoxic activity; Apoptosis; Antimicrobial activity; Antioxidant activity; Tar extracts